Lipidomics as a Tool for Functional Genomics in Sinorhizobium Meliloti - Saborido Basconcillo, Libia (My University, 2008)
This thesis focused on the development of comprehensive, rapid and simple methodologies for the analysis of fatty acids by gas chromatography mass spectrometry (GC/MS) and intact lipids by electrospray ionization tandem mass spectrometry (ESIIMS/MS). The methodologies were applied as a tool for functional genomics in the soil bacterium Sinorhizobium meliloti. The effects of inorganic phosphate (Pi)-starvation and acidity on lipid composition were studied.
A micro-scale, one-vial method for the analysis of fatty acids as their fatty acid methyl esters by GC/MS was developed. The method required small sample sizes, involved minimum handling and avoided tedious extraction steps, which increased sample throughput. A series of quality controls were included to measure losses due to handling, derivatization efficiencies and the extent of side reactions. The method was suitable for the analysis of sensitive bacterial fatty acids such as cyclopropane fatty acids.
A shotgun lipidomics approach was developed for the analysis of intact lipids by ESIIMS/MS. Fatty acid distributions were obtained for eight lipid classes and up to 58 individual lipids were identified in crude lipid extracts without sample cleanup or chromatography. For the first time, fatty acid distributions were provided for non-phosphorus containing lipids using shotgun lipidomics. Fatty acid distributions within lipid classes suggested that phospholipids and 1,2-diacylglyceryl-3-O-4'-(N,N,N-trimethyl)-homoserine lipids (TMHSs) were both synthesized from phosphatidic acid while sulfoquinovosyldiacylglycerol (SLs) had a different biosynthetic origin.
The methodologies were applied to study knockout mutants of five genes thought to participate in lipid metabolism in S. meliloti. It was demonstrated that: (1) cfa2 gene coded for the main cyclopropane fatty acyl synthase; (2) the plsC gene coded for a fatty acy 1 transferase specific for C 16 fatty acids in the sn-2 position of phospholipids; (3) a metabolic phenotype was revealed for knockout mutants of dme and tme genes (DME and TME, malic enzymes) when succinate was the carbon source.
Keywords: lipidomics; Sinorhizobium melilot; gas chromatography mass spectrometry; inorganic phosphate; functional genomics